Malheur National Wildlife Refuge, Public Land, and the Spaces of Whiteness - Smith, Joshua (Frontiers in Communication, 2021)
In this essay, I examine the 2016 takeover of Malheur National Wildlife Refuge. The principal instigators of this occupation, the Bundy family of Nevada, pointed to federally owned public lands as the primary reason for their takeover, citing the allegedly unconstitutional government ownership of these lands. I contend that the Bundys’ arguments about public lands exemplify rhetorical strategies that further one of the primary ends of settler colonialism; the remaking of land into property to better support white settlers’ claims to that land. I hold that the Bundys remake land by defining the land’s meanings following the logics of settler colonialism in three specific ways: privatization, racialization, and erasure. First, I examine the family’s arguments about the constitutionality of federal land ownership to show how the Bundys define public lands as rightfully private property. Second, I examine the ways that the Bundys racialize land ownership and how, in conjunction with arguments about property rights, the family articulates land as the domain of white settlers. Third, I discuss how the Bundys further colonial logics of Native erasure. That is, the family defines land in ways that portray Native Americans as having never been on the land, and are not currently using the land. I argue that these three processes render meanings of land––as private property, colonized, and terra nullius––that rhetorically further the operation of settler colonialism.